Stress and social behaviors of maternally deprived captive giraffes (Giraffa camelopardalis). Issue 2 (12th March 2018) - Siciliano‐Martina, Leila; Martina, Jason P.
Abstract : Maternal deprivation can cause long‐term behavioral changes in captive mammals. Studies regarding captive ungulates have also indicated behavioral shifts in the presence of the animal keeping staff; however, little is known about these effects in captive giraffes ( Giraffa camelopardalis ). To examine this, we observed a population of reticulated giraffes composed of maternally raised and maternally deprived individuals by direct and camera observations at Binder Park Zoo, Battle Creek, Michigan. We conducted observations using a unique ethogram with special regard for behaviors that might indicate stress or anti‐social tendencies. Several variables can interact to create behavioral changes; to account for this, our study design examined the interactive effects of observation technique, raising style, and temperature on giraffe behavior. The results of these observations showed a significant increase in the rate of stereotypic and antisocial behaviors resulting from the interaction of observation technique and raising style. Stereotypic behaviors in particular showed a marked increased during cooler temperatures among giraffes of all raising style. Likewise, raising style, observation technique, and their interaction significantly impacted the time spent rubbing the enclosure. The findings of this study suggest that captive giraffe behavior can be a complex response to multiple factors and studies only examining single factors might oversimplify behavioral shifts.